Novel Computational Methods for Modeling Gene Regulatory Interactions - Clauss, Benjamin. (Tufts University. Tisch Library., 2025)
Thesis (Ph.D.)--Tufts University, 2024-02.; Submitted to the Dept. of Genetics.; Advisors: Mingyang Lu, and Christopher Baker.; Committee: Amy Yee, and Gregory Carter.; Keyword: Biomedical engineering.